Given the equation \(x^5+5(2x^3+x+2)=5x^2(x^2+2)\) has a real root in the form of \(a-\sqrt[5]{b}\) where \(a\) and \(b\) are real positive integers. Find \((a,b)\)

Yes, it is best that you remember first few rows of the Pascal triangle. They are actual the binomial expansion coefficients, which is given by \(\begin{pmatrix} n \\ r \end{pmatrix}\). For example, when \(n=5\), we have:

## Comments

Sort by:

TopNewest\[x^5+5(2x^3+x+2)=5x^2(x^2+2)\\ x^5+10x^3+5x+10 = 5x^4+10x^2 \\ x^5 -5x^4+10x^3-10x^2+5x+10 = 0 \\ x^5 -5x^4+10x^3-10x^2+5x-1+1 +10 = 0 \\ (x-1)^5 = -11 \\ x-1 = - \sqrt [5] {11} \\ x = 1 - \sqrt [5] {11} \\ \Rightarrow \boxed{a = 1 \quad b = 11} \]

Log in to reply

Oh, so we have to know the \((x-1)^5\) factorization here right?

Log in to reply

Yes, it is best that you remember first few rows of the Pascal triangle. They are actual the binomial expansion coefficients, which is given by \(\begin{pmatrix} n \\ r \end{pmatrix}\). For example, when \(n=5\), we have:

\[\begin{equation} \begin{split} (x-1)^5 & = \sum_{r=0}^5 {(-1)^r\begin{pmatrix} 5 \\ r \end{pmatrix}x^{5-r}} \\ & = \begin{pmatrix} 5 \\ 0 \end{pmatrix}x^5 - \begin{pmatrix} 5 \\ 1 \end{pmatrix}x^4 + \begin{pmatrix} 5 \\ 2 \end{pmatrix}x^3 - \begin{pmatrix} 5 \\ 3 \end{pmatrix}x^2 + \begin{pmatrix} 5 \\ 4 \end{pmatrix}x^1 - \begin{pmatrix} 5 \\ 5 \end{pmatrix}x^0 \\ & = x^5 - 5x^4 + 10x^3 - 10x^2 + 5x - 1 \end{split} \end{equation} \]

Log in to reply

How you thought it will be (x-1)^5? Sir.

Log in to reply

Pascal triangle:

\[1 \\ 1 \quad 1 \\ 1 \quad 2 \quad 1 \\ 1 \quad 3 \quad 3 \quad 1 \\ 1 \quad 4 \quad 6 \quad 4 \quad 1 \\ 1 \quad 5 \quad 10 \quad 10 \quad 5 \quad 1\\ 1 \quad 6 \quad 15 \quad 20 \quad 15 \quad 6 \quad 1 \]

Log in to reply

Log in to reply